Identification of Biomarkers Related to CD8+ T Cell Infiltration With Gene Co-expression Network in Lung Squamous Cell Carcinoma - Tang, Min; Li, Yukun; Luo, Xianyu; Xiao, Jiao; Wang, Juan; Zeng, Xin; Hu, Qihao; Chen, Xiaoyan; Tan, Si-jie; Hu, Jun (Frontiers in Cell and Developmental Biology, 2021)
Lung squamous cell carcinoma (LSCC) is one of the most common types of lung cancer in adults worldwide. With the development of modern medicine, cancer treatment that harnesses the power of the immune system might be particularly effective for treating LUAD. In this research, LSCC expression data, which quantify the cellular composition of immune cells, were analysed by weighted gene coexpression network analysis (WGCNA) and a deconvolution algorithm based on the Gene Expression Omnibus (GEO) database, and the results indicated a close relationship between LSCC and CD8+ T cells. Six hub genes (SYT3, METTL8, HSPB3, GFM1, ERLIN2 and CLCN2) were verified by gene-gene network and protein-protein interaction network analyses. We found that the six hub genes were increased in cancer tissues and were closely correlated with cancer development and progression. After immune correlation analysis, METTL8 was selected as a prognostic biomarker. Finally, we found that the METTL8 levels were increased in multiple lung cancer cell lines and LSCC tissues. METTL8 inhibition could clearly induce G1 cell cycle arrest and suppress proliferation. Therefore, METTL8, which is related to CD8+ T cell infiltration, might be identified as a potential biomarker and gene therapy target in LSCC.